All‐Solid‐State Lithium Batteries: Electrochemical and Structural Analysis in All‐Solid‐State Lithium Batteries by Analytical Electron Microscopy: Progress and Perspectives (Adv. Mater. 27/2020). Issue 27 (7th July 2020) - Zhang, Chunchen; Feng, Yuzhang; Han, Zhen; Gao, Si; Wang, Meiyu; Wang, Peng
Abstract : In article number 1903747, Peng Wang and co‐workers describe the recent development of all‐solid‐state lithium battery characterization using scanning transmission electron microscopy (STEM). They highlight potential applications of combining cryogenics with phase‐contrast STEM imaging, such as ptychography, in which image‐forming optics are replaced by computational methods (like a "digital lens") using an array of electron diffractions collected by fast detectors. Cover illustration by Songhua Cai and Peng Wang.